Characterizing seed demand in Nigeria: Constraints, opportunities, and challenges - Salau, Sheu (International Food Policy Research Institute, 2009)
The Federal Government of Nigeria, through the FMAWR, envisions improving its food security by facilitating equitable access, availability and affordability of quality foods to all Nigerian. This vision has become more important as global food prices have risen. Achieving this vision requires deliberate and sustained efforts to improve agricultural productivity growth through strategic investments in the input system: seeds, fertilizer, and irrigation. While boosting production of good quality seed is one of the necessary steps towards improving agricultural productivity growth, the uptake of improved seeds by farmers is another very important activity. This is being slowed down by both supply and demand constraints within the sector.